Microelectrical Discharge Machining: A Suitable Process for Machining Ceramics. (31st August 2015) - Schubert, Andreas; Zeidler, Henning; Kühn, Ralf; Hackert-Oschätzchen, Matthias
Abstract : Today ceramics are used in many industrial applications, for example, in the biomedical field, for high-temperature components or for cutting tools. This is attributed to their excellent mechanical and physical properties, as low density, high strength, and hardness or chemical resistance. However, these specific mechanical properties lead to problems regarding the postprocessing of ceramics. In particular, cutting processes require expensive tools which cause high manufacturing costs to machine ceramics. Consequently, there is a demand for alternative machining processes. Microelectrical discharge machining (micro-EDM) is a thermal abrasion process which is based on electrical discharges between a tool and a workpiece. The advantages of micro-EDM are more and more in focus for ceramic machining. These advantages include the process of being a noncontact technology, an independency of material brittleness and hardness, a low impact on the material, and the achievable microstructures. This paper presents the current state of investigations regarding micro-EDM of ceramics. Beside the process principle of EDM, the used procedures for machining ceramics and insulating ceramics are described. Furthermore several machining examples are presented to demonstrate the possibilities of the micro-EDM process with regard to the machining of ceramics.